Sob o badalar dos sinos, o ar da modernidade. Ouro Preto: população, família e sociedade, 1838-1897 - Mirian Moura Lott (2009)
The objective of this study is to trace the social and cultural profile, and demographicbehavior of the population of the imperial city of Ouro Preto, in the second half of thenineteenth century, considered in an extended form, since the end of the third decade ofthat century. Thus, despite being the research focused in the second half of thenineteenth century, we use as the initial landmark the picture of Ouro Preto in 1838,because we have as a valuable source the nominal list for that year, which enables us touncover the population and social profile of the city, and we propose the date of 1897for completion of production, when the transfer of capital to Belo Horizonte determinesa radical break in the life of the residents of Ouro Preto. The city of Ouro Preto does not exist only as background of this study, but was chosen for its unique role as capital of the province of Minas Gerais. Besides a political center, Ouro Preto was a social and cultural reference to the population of Minas Gerais, although no longer was an economic center, leaving that position to other regions of the province, as the south and of São João del Rei. Following the research line proposed by the Social History of Culture, we intend touncover and discuss the behavior and social practices of the population of Ouro Preto,and observe the cultural changes, in view of the profound changes in international andnational overviews of the period. The sources used are the records of baptisms, marriages and deaths of the parish of Nossa Senhora do Pilar of Ouro Preto, the nominal list of 1838, the first general census of the Empire in 1872, and the new census of 1890. We also use the maps of population that, if not directly comprehend the capital of Minas Gerais, at least presents the profile of the central region of the province. The serial and population documentation allow us two kinds of analysis: the quantitative, which allows presentation of more general social characteristics, trends of cultural changes, and qualitative, through which we discovered the particularities and specificities approaching us to those people of the past, highlighting the conflicts, anxieties and tensions of that society. The area covered is the urban core of Ouro Preto, despite the vastness of the parish of Pilar allows us to investigate aspects of more distant chapels, such as Santa Quitéria the camp of Boa Vista and of Our Lady of Rodeo, located in districts belonging to that parish. The monitoring of the sources, during the proposed period, also gives us opportunity to see their history, both in terms used in their texts, that suit the administrative measures, such as in the emphasis on certain information contained in the documents. From the internal study of the sources, we look at the specific concern of each period. Information totally absent in some periods (such as the degrees of relationship or age of the bride and groom for the wedding records), appear in others with accuracy and consistency, disappearing after a few years. The specificities of the baptisms of naïve (children of slave mothers after the Lei do Ventre Livre) and deaths of slaves, even in the seventh decade of the nineteenth century, enables us to insert ourselves in the concerns of men of that time.